2003
DOI: 10.1523/jneurosci.23-24-08568.2003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Coupling between Sulfonylurea Receptor Type 1 and a Nonselective Cation Channel in Reactive Astrocytes from Adult Rat Brain

Abstract: We previously identified a novel, nonselective cation channel in native reactive (type R1) astrocytes (NR1As) from injured rat brain that is regulated by cytoplasmic Ca2+ and ATP (NC(Ca-ATP)) and exhibits sensitivity to block by adenine nucleotides similar to that of sulfonylurea receptor type 1 (SUR1). Here we show that SUR1 is involved in regulation of this channel. NR1As within the site of injury and after isolation exhibited specific binding of FITC-tagged glibenclamide and were immunolabeled with anti-SUR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
191
1
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(208 citation statements)
references
References 36 publications
9
191
1
7
Order By: Relevance
“…The opening of SUR1/TRPM4 channels causes complete depolarization and cell blebbing, characteristic of cytotoxic (cellular) edema. Depolarization and blebbing induced by depletion of ATP are prevented by glibenclamide, consistent with a crucial role for SUR1/ TRPM4 channels in cytotoxic edema [71,72]. SUR1/ TRPM4 channels represent an important path for sodium flux required for formation of edema, and independent of Na + -K + -ATPase inactivity seen in ischemia.…”
Section: Nkcc1mentioning
confidence: 54%
“…The opening of SUR1/TRPM4 channels causes complete depolarization and cell blebbing, characteristic of cytotoxic (cellular) edema. Depolarization and blebbing induced by depletion of ATP are prevented by glibenclamide, consistent with a crucial role for SUR1/ TRPM4 channels in cytotoxic edema [71,72]. SUR1/ TRPM4 channels represent an important path for sodium flux required for formation of edema, and independent of Na + -K + -ATPase inactivity seen in ischemia.…”
Section: Nkcc1mentioning
confidence: 54%
“…Opening of NC Ca-ATP channels causes complete depolarization and cell blebbing, characteristic of cytotoxic edema. Depolarization and blebbing induced by depletion of ATP are prevented by glibenclamide, and are reproduced without depletion of ATP by diazoxide, consistent with a crucial role for NC Ca-ATP channels in cytotoxic edema 3 .…”
mentioning
confidence: 59%
“…2b). Apart from its involvement in K ATP channels, SUR1 also forms the regulatory subunit of NC Ca-ATP channels 3 . As the pore-forming subunit of the NC Ca-ATP channel has not been cloned, we used its biophysical properties for identification.…”
Section: Nc Ca-atp Channel In Neurons After Mcaomentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggested that mitochondrial ATP-sensitive potassium channels served as the target for diazoxide in the astrocytes [13]. On the other hand, another recent investigation has revealed the possibility that ATP-sensitive non-selective cation channels on the surface of reactive astrocytes could be regulated by sulfonylurea receptor-1, which is the site of action of diazoxide [3]. These data suggest that diazoxide can target both mitochondrial and surface cation channels on the astrocytes, thereby modulating the astrocytic function, which could explain our present data.…”
mentioning
confidence: 97%